The Use of Audio-Visual Media to Increase the Participation of Less Active Students in Phase A English Learning in Grade II at MI Nurul Mun'im Karanganyar Paiton - Asri kandi; Bradhiansyah Tri Suryanto; Fa’ikoh Sholiha (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to increase the participation of less active students in English learning in Class II of MI Nurul Mun'im Karanganyar Paiton through the use of audiovisual media. The method used is Classroom Action Research (CAR) which is carried out in two cycles, each of which includes the stages of planning, implementation of actions, observation, and reflection. There were 21 students participating in this study. Data were collected through observation of student activities, learning documents, student assignments, and pre- and post-tests based on the Prota and Promes. The results showed a significant increase in student participation and engagement after the implementation of audiovisual media. This improvement was evident from the increased activity of students during the learning process and the increase in the number of students who achieved the Minimum Passing Grade (KKM) of 65 in cycle II. Thus, audiovisual media proved to be effective in increasing student participation and learning outcomes, especially for students who were previously less active in English learning